Fish Pluripotent Stem-Like Cell Line Induced by Small-Molecule Compounds From Caudal Fin and its Developmental Potentiality - Xu, Wenting; Li, Huajin; Peng, Liangyue; Pu, Liyu; Xiang, Sijia; Li, Yue; Tao, Leiting; Liu, Wenbin; Liu, Jinhui; Xiao, Yamei; Liu, Shaojun (Frontiers in Cell and Developmental Biology, 2022)
The technique of induced pluripotent stem cells has significant application value in breeding and preserving the genetic integrity of fish species. However, it is still unclear whether the chemically induced pluripotent stem cells can be induced from non-mammalian cells or not. In this article, we first verify that fibroblasts of fish can be chemically reprogrammed into pluripotent stem cells. These induced pluripotent stem-like cells possess features of colony morphology, expression of pluripotent marker genes, formation of embryoid bodies, teratoma formation, and the potential to differentiate into germ cell-like cells in vitro. Our findings will offer a new way to generate induced pluripotent stem cells in teleost fish and a unique opportunity to breed commercial fish and even save endangered fish species.